Características de los animales domésticos - Mendez Ybañez, Ylla Cori (2019)
The children in their initial educational formation, have a lot of contact with the domestic_x000D_ animals, so it is particularly important that they know and identify their main characteristics and the habitat where they develop; as a way to interrelate and understand_x000D_ that they are part of the environment where they operate. Through the elaborated learning session, it s main purpose is to teach them the characteristics of the domestic animals of their locality, so that the children understand,_x000D_ that through a proper care and treatment, they will be able to preserve them and that they adapt better to the domestic environment in which they develop. Being the respective indicator: describe the characteristics and needs of living beings to live and identify which domestic animals exist in their locality.